The Relationship of Self-Care Behaviours and Online Learning Engagement Among Nursing Students During the COVID-19 Pandemic - Mazlinda Musa; Rohani Mamat; Hamidah Hassan; Siti Fatimah Sa’at; Syed Syarizman Abd Rahim; Abdul Rahman Ramdzan; Octovia Abdullah; Vellerina Ally Paidius; Mariana Muitaba; Ashley Melissa George (Jurnal Keperawatan Indonesia, 2023)
The COVID-19 pandemic and the sudden switch from conventional to virtual classes allegedly raised students' risk of mental health illnesses, adversely influencing their academic engagement and learning outcomes. Nursing students in Malaysia, especially those enrolled in universities in Sabah, have traditionally been accustomed to a conventional face-to-face teaching and learning approach. Due to the COVID-19 pandemic, e-learning or online classes have become one of the learning methods for university nursing students in Sabah, either while they are on campus or at home, to obtain access for educational purposes. The purpose of this study was to assess the relationship between self-care behaviours and online class engagement among the university nursing students in Sabah throughout the pandemic. This study was a quantitative descriptive cross-sectional study that used the Mindful Self-Care Scale (MSCS) and the Online Student Engagement Scale (OSE). SPSS version 26. Pearson Correlation analysis showed moderate level of positive relationship (r = 0.582, p = < 0.001, n = 120). Adequate evidence exists to show that level of self-care is positively moderately related to the online classes’ engagement behaviour among the nursing students in this study. Students should possess the self-control to set goals, effectively allocate their time, and avoid procrastination. Keywords:  online classes, online engagement, pandemic, self-care   Abstrak Hubungan Perilaku Perawatan Mandiri dan Keterlibatan Pembelajaran Online di antara Mahasiswa Keperawatan Universitas di Sabah Selama Pandemi COVID-19. Pandemi COVID-19 dan peralihan tiba-tiba dari kelas konvensional ke kelas virtual diduga meningkatkan risiko penyakit kesehatan mental siswa, yang secara negatif memengaruhi keterlibatan akademik dan hasil belajar mereka. Mahasiswa keperawatan di Malaysia, khususnya mahasiswa keperawatan universitas di Sabah, telah terbiasa dengan pengajaran dan pembelajaran tatap muka. Di tengah pandemi COVID-19, e-learning atau kelas online menjadi salah satu metode pembelajaran bagi mahasiswa keperawatan universitas di Sabah, baik di kampus maupun di rumah, untuk mendapatkan akses untuk keperluan pendidikan. Tujuan dari penelitian ini adalah untuk menilai hubungan antara perilaku perawatan mandiri dan keterlibatan kelas online di kalangan mahasiswa keperawatan universitas di Sabah selama pandemi. Penelitian ini merupakan penelitian cross-sectional deskriptif kuantitatif dengan menggunakan Mindful Self-Care Scale (MSCS) dan Online Student Engagement Scale (OSE). SPSS versi 26 Pearson Correlation menunjukkan tingkat hubungan positif sedang (r = 0,582, p = < 0,001, n = 120). Ada bukti yang memadai untuk menunjukkan bahwa tingkat perawatan mandiri secara positif terkait dengan perilaku keterlibatan kelas online di antara mahasiswa keperawatan dalam penelitian ini. Kata Kunci: kelas online, keterlibatan online, pandemi, perawatan mandiri